Evaluation of hydraulic conductivity for both marine and deltaic deposits based on piezocone testing. (1st December 2015) - Shen, Shui-Long; Wang, Jun-Peng; Wu, Huai-Na; Xu, Ye-Shuang; Ye, Guan-Lin; Yin, Zhen-Yu
Abstract: In order to rapidly determine the hydraulic conductivity for both marine and deltaic deposits in field, an approach is proposed to evaluate the hydraulic conductivity of soil using cone penetration tests with pore water pressure measurement, known as piezocone testing. This approach is based on the test results from a series of laboratory penetration tests investigating the expansion shape of soil using a model cone tip with different tip angles and considering the influence of the soil characteristics. To derive the calculation method, two assumptions are made: i ) the flow surface of pore water is assumed to be a half ellipsoid shape, covering the whole tip of the cone, and ii ) the initial state of induced excess pore pressure is assumed to be have a negative exponential distribution and to dissipate from the half ellipsoid surface. The proposed approach is compared with the existing approach based on piezocone data and laboratory testing. All of the three methods were applied to analyze three field cases, in which two cases is marine deposit and one is deltaic deposit. The results show that the proposed approach can predict hydraulic conductivity of both marine and on-land deposit, which extends the range of the application of the existing approaches as proposed by Chai et al. Highlights: Half ellipsoid distribution surface of pore water is assumed based on observed results. The initial distribution of excess pore pressure during penetration is assumed in a negative exponent distribution. A generalized approach is proposed to evaluate hydraulic conductivity of both marine and deltaic soils based on piezocone test. The proposed method is verified from three field cases based on both field and laboratory test.